Early neurological deterioration following thrombolysis for minor stroke with isolated internal carotid artery occlusion. (14th October 2020) - Boulenoir, N.; Turc, G.; Henon, H.; Laksiri, N.; Mounier‐Véhier, F.; Girard Buttaz, I.; Duong, D.‐L.; Papassin, J.; Yger, M.; Triquenot, A.; Lyoubi, A.; Ter Schiphorst, A.; et al.
Abstract : Background and purpose: Better understanding the incidence, predictors and mechanisms of early neurological deterioration (END) following intravenous thrombolysis (IVT) for acute stroke with mild symptoms and isolated internal carotid artery occlusion (iICAo) may inform therapeutic decisions. Methods: From a multicenter retrospective database, we extracted all patients with both National Institutes of Health Stroke Scale (NIHSS) score <6 and iICAo (i.e. not involving the Willis circle) on admission imaging, intended for IVT alone. END was defined as ≥4 NIHSS points increase within 24 h. END and no‐END patients were compared for (i) pre‐treatment clinical and imaging variables and (ii) occurrence of intracranial occlusion, carotid recanalization and parenchymal hemorrhage on follow‐up imaging. Results: Seventy‐four patients were included, amongst whom 22 (30%) patients experienced END. Amongst pre‐treatment variables, suprabulbar carotid occlusion was the only admission predictor of END following stepwise variable selection (odds ratio = 4.0, 95% confidence interval: 1.3–12.2; P  = 0.015). On follow‐up imaging, there was no instance of parenchymal hemorrhage, but an intracranial occlusion was now present in 76% vs. 0% of END and no‐END patients, respectively ( P  < 0.001), and there was a trend toward higher carotid recanalization rate in END patients (29% vs. 9%, P  = 0.07). As compared to no‐END, END was strongly associated with a poor 3‐month outcome. Conclusions: Early neurological deterioration is a frequent and highly deleterious event after IVT for minor stroke with iICAo, and is of thromboembolic origin in three out of four patients. The strong association with iICAo site—largely a function of underlying stroke etiology—may point to a different response of the thrombus to IVT. These findings suggest END may be preventable in this setting. Abstract : In this multicentre observational study including 74 patients with isolated internal carotid artery occlusion (i.e. without associated intracranial occlusion) with minor baseline symptoms (NIHSS score <6) and treated with IV‐thrombolysis, Early Neurological Deterioration (END) within 24hrs occurred in 30% of patients and was strongly associated with poor 3‐month outcome. The predominant END mechanism was thrombo‐embolic, as evidenced by a new intracranial occlusion in 3 out of 4 END cases. Supra‐bulbar carotid occlusion site –largely a function of underlying stroke etiology– was the only predictor of END, which may point to a different response of the thrombus to IV‐thrombolysis.